The ugly truth about social welfare payments and households' subjective well-being - Tamanna Adhikari; Talita Greyling; Stephanie Rossouw (Global Labor Organization (GLO), 2021)
Social welfare payments (SWP) were designed with policy priority to transfer revenue to vulnerable groups, thereby addressing poverty and inequality. Previous studies have shown that SWPs alleviate poverty, but investigating their effect on well-being is sparse. We investigate the relationship between SWPs and the mean subjective well-being (SWB) of a household and analyse it across household income quintiles. We use the National Income Dynamics Study dataset, which is representative of South Africa. South Africa is an example of extremes, as it suffers from poverty, inequality, and low levels of SWB; yet, paradoxically, it has an exemplary social welfare system. We use a range of analytical methods, including ordered probit regressions and a quasi-experimental technique. We find that the highest household income quintiles claim SWPs meant for the poor, most likely leading to increased inequality. Additionally, SWPs are positively related to SWB for quintiles one to four, but the relationship is negative in the highest quintile.
Keywords: I31; J13; J18; 330; Subjective well-being; social welfare payment; quasi-experiment; South Africa